Flow field analysis and testing of curved shroud wind turbine with different flange angle. Issue 1 (31st December 2022) - Heyru, Beshir; Bogale, Wondwossen
Abstract: This research focuses on computational fluid dynamics modeling and experimental analysis of a shrouded wind turbine. A shroud turbine comprises a wind turbine with a flanged shroud encircling it for better wind energy utilization at low wind speed. The effects of diffuser shape and flange angle have been studied by performing flow field analysis in Ansys Fluent for better utilization and condensing of the shroud size. The CFD analysis shows that a cycloid diffuser shape gives 7% more velocity than a straight shape. In addition, the optimum flange angle for a cycloid diffuser is +10°, while compared with the normal flange angle, the optimal flange angle has increased velocity and power by 4.83% and 15%, respectively. This increment is due to the variation in the magnitude of vortex generation behind the flange. Besides, the performance of the proposed 3D, shrouded, and unshrouded wind turbines was numerically analyzed, and a prototype model for the proposed wind turbines was manufactured and tested. The simulation and experimental results agree and lay within the acceptable range. Compared with an unshrouded wind turbine with a similar swept area and wind speed, the shrouded wind turbine increased velocity and power by 1.58 and 5, respectively. This increase in speed and power makes the shrouded turbine suitable for application in low wind speed areas. Moreover, it can be helpful in sparsely populated off-grid areas to generate electricity by being mounted on rooftops.